2011
DOI: 10.4103/2231-0754.121861
|View full text |Cite
|
Sign up to set email alerts
|

Screening of gingival crevicular blood glucose and capillary finger blood glucose in the diagnosis of diabetes

Abstract: Aim:The study aimed at obtaining glucose readings using gingival crevicular blood (GCB) to screen for undiagnosed diabetes during routine dental visits. Materials and Methods: The present study included 50 patients who were divided into two groups, i.e. Group A and Group B, based on bleeding on probing at the site of collection of GCB. Group A participants had blood collected from sites having adequate bleeding on probing, whereas Group B participants had blood collected from sites with little bleeding on prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…For example, Rapone et al [ 9 ], who examined the correlation in people with a positive BOP, found this correlation convincing in those with diabetes. Waghmare et al [ 15 ] also found that the above correlation was acceptable in people with heavy bleeding gums. In the studies of Saeed et al [ 3 ], Singh et al [ 10 ], Nayagam et al [ 11 ], Sibyl et al [ 25 ], Subodh et al [ 13 ], Kaur et al [ 26 ], Ardakani et al [ 21 ], and Beikler et al [ 27 ], all participants had stage 2 grade B to stage 3 grade C periodontitis and included patients diagnosed with diabetes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Rapone et al [ 9 ], who examined the correlation in people with a positive BOP, found this correlation convincing in those with diabetes. Waghmare et al [ 15 ] also found that the above correlation was acceptable in people with heavy bleeding gums. In the studies of Saeed et al [ 3 ], Singh et al [ 10 ], Nayagam et al [ 11 ], Sibyl et al [ 25 ], Subodh et al [ 13 ], Kaur et al [ 26 ], Ardakani et al [ 21 ], and Beikler et al [ 27 ], all participants had stage 2 grade B to stage 3 grade C periodontitis and included patients diagnosed with diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…The FCBG values obtained in this study were higher than the GCBG values in each periodontal group and in total. Studies by Singh et al [ 10 ], Parihar et al [ 22 ], Kaur et al [ 26 ], and Waghmare et al [ 15 ] also reported higher values for FCBG than GCBG.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Almost two-thirds of the general population visit a dentist’s office for a variety of reasons, including routine cleaning and treatment for a toothache. Introducing means to screen for T2DM at dental clinics can be a means of early detection and diagnosis of T2DM [5-6]. Uncontrolled T2DM is a factor in gum disease development; conversely, untreated gum disease can increase HbA1c levels by as much as 1%.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have investigated this relationship with varying results, we incorporated a larger portion of our community to enhance our study. We used office-based glycosylated hemoglobin (HbA1c) laboratory machines for ease of access, quick results to diagnose, and arranged timely follow-ups with a primary care physician [5-6].…”
Section: Introductionmentioning
confidence: 99%